2007
DOI: 10.1016/j.expneurol.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral functional deficits following closed head injury in the neonatal pig

Abstract: Neurobehavioral deficits in higher cortical systems have not been described previously in a large animal model of diffuse brain injury. Anesthetized 3-5 day old piglets were subjected to either mild (142 rad/sec) or moderate (188 rad/sec) rapid non-impact axial rotations of the head. Multiple domains of cortical function were evaluated 5 times during the 12 day post-injury period using tests of neurobehavioral function devised for piglets. There were no observed differences in neurobehavioral outcomes between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 35 publications
5
67
1
Order By: Relevance
“…Large animals are commonly used as experimental models for human-infant research into brain disorders (pig, Lind et al 2007), sudden infant death syndrome (pig, Tong et al 1995), head injury (Lehman et al 2002), brain injury induced by hypoxia (pig, Foster et al 2001; www.intechopen.com sheep, Laurini et al 1999) or by preterm birth (sheep, Patural et al 2010, Pladys et al 2008, Riddle et al 2006, and neurobehavioural topics (pig, Friess et al 2007). They can also be used for xenografts in Parkinson's disease (Molenaar et al 1997).…”
Section: Brain Injurymentioning
confidence: 99%
“…Large animals are commonly used as experimental models for human-infant research into brain disorders (pig, Lind et al 2007), sudden infant death syndrome (pig, Tong et al 1995), head injury (Lehman et al 2002), brain injury induced by hypoxia (pig, Foster et al 2001; www.intechopen.com sheep, Laurini et al 1999) or by preterm birth (sheep, Patural et al 2010, Pladys et al 2008, Riddle et al 2006, and neurobehavioural topics (pig, Friess et al 2007). They can also be used for xenografts in Parkinson's disease (Molenaar et al 1997).…”
Section: Brain Injurymentioning
confidence: 99%
“…In vivo and in vitro animal studies have identified mechanisms of TBIs associated with single rapid head acceleration-decelerations, similar to what might be experienced in a motor vehicle crash, [13][14][15][16][17][18][19][20] but only a few experimental studies have investigated TBI from repetitive back-and-forth motions of the head. Smith and associates 21 developed a shaking model of brain injury using male Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33]35 Because of the similarities between the brains of piglets and immature humans, the animal model has been used extensively to investigate mechanisms of pediatric TBI associated with single, nonimpact, rapid head rotations and has successfully identified key attributes of TBI, including the influence of head rotation direction, 14,36,37 changes with developmental age, 16,19,36 changes with post-injury time, 36,38 and behavioral consequences of this injury mechanism. 15,[39][40][41] Injuries reported in these studies include hypoxic-ischemic damage, widespread AI, large unilateral/bilateral subdural and subarachnoid hemorrhage, and ocular hemorrhage. 42 All of these TBI-associated injuries in the piglet resulted from single head rotations at very high velocities (160-200 rad/sec) and high-magnitude, rapid decelerations, similar to those in high-force accidental trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The previous axial plane studies generally showed decreases in exploratory behaviors as well, but the overall injury effect was not significant. 10,11 This indicates that the sagittal plane injury produced greater exploratory deficits than the axial plane injury. The persistence of these exploratory deficits to day + 4 post-injury in the sagittally injured animals despite the abatement of motor deficits, indicates that decreases in exploration may arise, at least in part, from cognitive sources, and suggests greater persistent cognitive impairment in sagittal plane injuries than in axial plane injuries.…”
Section: Direction Dependence Of Behavior and Axonal Injurymentioning
confidence: 99%
“…[7][8][9] Whereas the porcine model has many advantages, there is limited information available regarding immature porcine behavior following TBI. Open field testing has demonstrated that injured piglets have a decreased interest in exploring their environment, 10 and that piglets with multiple brain injuries showed deficits in attention and short-term memory in a T-maze task. 11 The further characterization of porcine behavior post-TBI will greatly increase the value of this model.…”
mentioning
confidence: 99%